(untitled) (Bangladesh Journal of Child Health, 2024)
Background: Anaemia is a common childhood health problem. Among the causes of anaemia besides the nutritional anaemia congenital hemoglobin disorder such as thalassemia and haemoglobinopathies has a great role which can be combated by increasing awareness in the population. Objective: To detect clinical features, common causes, risk factors of childhood anaemia and to make awareness among the population to prevent the deadly effects of anaemia in children as well as in the society. Methodology: A cross-sectional study was carried out at outpatient department of Delta Medical College and Hospital over a period of 3 years. Children aged between 6 months to eighteen years who visited outdoor for acute illness and were clinically pale and CBC supporting the condition were included. Children with malignancy and haemorrhagic diseases were excluded from the study. Total 200 cases were collected. Results: Among 200 cases 62.5% were male. Most vulnerable age group was 6 months to 2 years (63%). Most common cause of anaemia was iron deficiency anaemia (64.5%). Congenital haemoglobin disorder was the second most common cause (28%). Among haemoglobinopathies Hb E trait contributes (82.35%). Most common presentation of anaemic children was frequent attack of RTI. Low protein diet was the most common risk factor for iron deficiency anaemia. Under five years, males were more affected but thereafter females were more affected than male children. Among 200 cases only 32(15%) cases were malnourished. Most of the cases were term baby. Among inherited cases only one care giver had knowledge about thalassemia. Most cases came from lower middle class family (65%). Most common morphologic variant of anaemia was microcytic hypochromic anaemia (99%). RBC count was normal in iron deficiency anaemia. Conclusion: Besides iron deficiency anaemia, haemoglobinopathies and thalassemia have a great contribution in childhood anaemia. Family education, increased awareness, screening out of thalassemia and haemoglobinopathies carrier can combat this heath problem in children and can reduce social burden. Bangladesh J Child Health 2023; Vol 47 (2) : 89-94